Polynomial Stability and Numerical Analysis of a Coupled Wave System with Weak Dissipative Term - Guardia Cayo, Andrés (2025)
This article investigates, within the context of numerical analysis, qualitative aspects of the solutions to a one-dimensional model of coupled wave propagation with weak dissipation. In this system, one of the equations is conservative, while the other incorporates frictional dissipation. The main objective is to determine under which conditions the full finite difference discretization preserves the qualitative behavior of the system’s energy.